قلق المستقبل وعلاقته بتفكير الطلبة نحو الهجرة الغير شرعية - منصوري, نبيل; طراد, توفيق; العمري, عبد النور (جامعة الوادي - University of Eloued, 2021)
الملخص: هدفت الدراسة الحالية إلى التعرف على مستوى قلق المستقبل وانعكاسه على توجه الطلبة نحو الهجرة الغير شرعية، في الشق الميداني للدراسة تم استخدام المنهج الوصفي التحليلي على عيينة عشوائية من 300 طالب وطالبة وطبق عليهم مقياس قلق المستقبل المهني المعد من طرف الباحثتان (سهيلة، سالمي2015)، واستبيان معد من طرف الباحثين للكشف عن تأثير قلق المستقبل على توجه الطلبة نحو الهجرة الغير شرعية وتم تحليل البيانات باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعي لحساب كا2 والنسبة المئوية واختبار(ت) لدلالة الفروق بين المتوسطات والمتوسط الحسابي والانحراف المعياري، وتوصلت النتائج إلى:1- مستوى قلق المستقبل مرتفع عند الطلبة .2- ينعكس قلق المستقبل على تفكير الطلبة نحو الهجرة الغير شرعية. وفي ضوء النتائج أوصى الباحثون: 1- محاولة الخفض من الأفكار السلبية نحو المستقبل المهني، من خلال البناء الواقعي للأهداف الاعتماد على برامج تربوية للتعريف بقلق المستقبل و آثاره السلبية و المضاعفات التي قد تنتج عنه. 2- توعية الطلاب الجامعيين بأساليب خفض قلق المستقبل . Abstract: The present study aimed to identify the level of future anxiety and its reflection on students ’orientation towards illegal immigration. In the field part of the study, the descriptive analytical method was used on a random sample of 300 students and applied to them the measure of future professional anxiety prepared by the two researchers (Suhaila, Salmi 2015 ), And a questionnaire prepared by researchers to reveal the effect of future anxiety on students' tendency towards illegal immigration, and the data was analyzed using the Statistical Package for Social Sciences (SPSS) program to calculate the Ca2 and the percentage and the (T) test for the significance of the differences between the averages, the arithmetic mean and the standard deviation, and the results were reached. To: 1- The level of future anxiety is high for students. 2- The anxiety of the future is reflected in students ’thinking about illegal immigration. In light of the results, the researchers recommend. 1- trying to reduce negative thoughts about the professional future. Through realistic construction of goals, reliance on educational programs to define future anxiety and its negative effects and complications that may result from it. 2- Educating university students about ways to reduce future anxiety.
مقال
Keywords: قلق المستقبل؛ الهجرة الغير شرعية؛ الطلبة; uture anxiety; illegal immigration ; students